Pidana Penipuan, Jual Beli 2; PENIPUAN DALAM JUAL BELI KAVLING TANAH YANG DILAKUKAN PENGEMBANG PERUMAHAN KEPADA KONSUMEN: PENIPUAN DALAM JUAL BELI KAVLING TANAH YANG DILAKUKAN PENGEMBANG PERUMAHAN KEPADA KONSUMEN - rahmad, noorramad; Setiyawan, Deni (JUSTISI, 2022)
The main purpose of this study is to find out the basics and legal elements for housing developers who commit fraud in the sale and purchase of plots of land and how to be responsible for housing developers who commit fraud in the sale and purchase of land lots. This study uses a normative juridical research method with a status approach and a case approach. The materials used in this study came from primary legal materials, secondary legal materials and non-legal materials. The research findings are related to the legal basis and elements regarding the fraudulent act of buying and selling land plots by housing developers to consumers, contained in Article 378 of the Criminal Code and Law Number 8 of 1999 concerning Consumer Protection Article 62 and the fulfillment of elements of fraud committed by owner of PT. ABC (property developer), so that his actions can be accounted for by article 378 of the Criminal Code and Law Number 8 of 1999 concerning Consumer Protection article 62. Recommendations : first, the legal basis for developers who commit fraud in the sale and purchase of residential plots of land. Second, the elements of criminal acts of fraud committed by housing developers. Third, the responsibility of housing developers who commit fraud in the sale and purchase of plots of land. In line with the conclusions above, it is hoped that it will be used as learning material and add insight into the criminal fraud of buying and selling land plots by housing developers to consumers.